Shockwaves evolving on nanosecond timescales around individual micro-discharge filaments in deionised water. (5th May 2021) - Hoffer, Petr; Prukner, Václav; Schmidt, Jiří; Šimek, Milan
Abstract: In this study, we present an analysis of the pressure fields developing around nanosecond discharges produced in deionised water by positive high-voltage pulses (+130 and +170 kV) with a fast rise time on a tungsten anode pin. Shockwaves and their associated pressure characteristics were investigated by laser interferometry with a very high spatial resolution of 0.8 μ m utilising the concept of a picosecond Mach–Zehnder interferometer based on a Nd:YAG laser (532 nm, 30 ps). Shifts of the fringes in interference patterns due to variations in the refractive index of liquid water produced in the vicinity of the tungsten anode were projected by the interferometer and analysed as a function of the pressure. High spatial resolution combined with the picosecond laser pulse allowed for the examination of frozen interferometric characteristics of cylindrical shockwaves. Consequently, unique results characterising the shockwaves developing around individual discharge filaments were obtained. For easier comparison, the shockwave pressures were normalised to a radius of 0.4 μ m, which was found as the most probable maximum of initial radius of primary dark filament. At this radius, the most probable shock pressure was 1.5 GPa, whereas the highest obtained shock pressure reached 11 GPa. We showed that the modified Gaussian distribution fits the obtained results well. Finally, we observed that most of those extraordinary strong shock-fronts were associated with the dark filaments containing strong residual plasma-induced emission. This observation likely provides an indirect evidence of the electrostriction-assisted discharge onset mechanism.